A Selective Deficit in Phonetic Recalibration by Text in Developmental Dyslexia - Keetels, Mirjam; Bonte, Milene; Vroomen, Jean (Frontiers in Psychology, 2018)
Upon hearing an ambiguous speech sound, listeners may adjust their perceptual interpretation of the speech input in accordance with contextual information, like accompanying text or lipread speech (i.e., phonetic recalibration; Bertelson et al., 2003). As developmental dyslexia (DD) has been associated with reduced integration of text and speech sounds, we investigated whether this deficit becomes manifest when text is used to induce this type of audiovisual learning. Adults with DD and normal readers were exposed to ambiguous consonants halfway between /aba/ and /ada/ together with text or lipread speech. After this audiovisual exposure phase, they categorized auditory-only ambiguous test sounds. Results showed that individuals with DD, unlike normal readers, did not use text to recalibrate their phoneme categories, whereas their recalibration by lipread speech was spared. Individuals with DD demonstrated similar deficits when ambiguous vowels (halfway between /wIt/ and /wet/) were recalibrated by text. These findings indicate that DD is related to a specific letter-speech sound association deficit that extends over phoneme classes (vowels and consonants), but – as lipreading was spared – does not extend to a more general audio–visual integration deficit. In particular, these results highlight diminished reading-related audiovisual learning in addition to the commonly reported phonological problems in developmental dyslexia.